Molecular Characterization of Diatom, Pseudo-Nitzschia Species (Bacillariophyceae) Based on Secondary Structures Modeling of Second Internal Transcribed Spacer (ITS2) Transcript - Teng, Sing Tung (Universiti Malaysia Sarawak, UNIMAS, 2010)
Diatoms in the genus Pseudo-nitzschia have been known as the causative organism in amnesic shellfish poisoning (ASP) events. Ten out of nearly 30 species thus far described have the ability to produce the potent neurotoxin, domoic acid. In Malaysia, however, has little attention paid to this form of shellfish poisoning. In this study, homologous modeling and free energy minimization approaches were used to model the secondary structure of the second internal transcribed spacer (ITS2) of Pseudo-nitzschia species. A total of 18 strains of Pseudo-nitzschia spp. from Borneo were cultured and genomic extracted. Gene amplification and sequencing of the ITS region of ribosomal RNA genes was carried out. Sequences obtained and related sequences were used to construct the secondary structure of ITS2 transcript. The results showed that the secondary structure predicted from Psedudo-nitzshia spp. consist four main paired helices with one pseudo-helix. Three motifs were found in the transcript. The common eukaryotic motif in the right of helix II with additional AAA was also found in all the structures. The structural analysis also showed conserved 5.8S-28S complex. The structural information was incorporated into the multiple sequence-structure alignment for phylogenetic analysis. The phylogenetic trees revealed two monophyletic clades. This was well supported by the morphological classification and the large subunit phylogentic evidences. Placement of some Pseudo-nitzschia spp. however remained unresolved. The ITS2 secondary structures information in this study provided better understanding of the Pseudo-nitzschia taxonomy and could be potential molecular tools in strain or species identification.